2019
DOI: 10.11591/ijeecs.v13.i2.pp453-460
|View full text |Cite
|
Sign up to set email alerts
|

The use of enhancement material in grounding system: a review

Abstract: <p>This paper reviews the improvement of grounding impedance in grounding system by means of enhancement materials. Various enhancement materials for the past 20 years will be reviewed according to their advantages and disadvantages, followed by a focus on the technique for proper measurement set up based on the standard. In addition to that, the condition of enhancement materials under high voltage exposure is reviewed. Many researchers claim that soil resistivity, moisture content, and surrounding envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This condition indicates that the vitric tuff resistivity is influenced by moisture content. The higher the resistivity, the lower the resistivity (Azmi et al, 2019;IEEE Standards Association, 2012).…”
Section: Fls Flsmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition indicates that the vitric tuff resistivity is influenced by moisture content. The higher the resistivity, the lower the resistivity (Azmi et al, 2019;IEEE Standards Association, 2012).…”
Section: Fls Flsmentioning
confidence: 99%
“…The strong La Nina phenomenon also affects clouds and precipitation to increase lightning intensity (Ghosh et al, 2019). The high activity of lightning can cause danger, so lightning protection is needed (Azmi et al, 2019;Bakar et al, 2020). Lightning protection aims to protect and reduce the risk of harm to living things, buildings, electricity, electronic equipment, telecommunications, and lightning activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have lately begun investigating if the waste product may be used in a grounding system. In the reduction of grounding resistance, several types of industrial waste products have been identified [18]. Fly ash is produced when coal is burned in a power station.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the behaviour of grounding systems an objective for different investigations, and which have been improved by several simulations and practical tests cited as follow: Ramlee et al [3] have studied the use of multiple grounding points on the lightning phenomenon. Azmi et al [4] have improved the grounding system impedance by adding enhancement materials in the surrounding of the studied electrode. Parise et al [5] have studied the efficiency of grounding system safety by studying the step/touch voltages in the studied system.…”
Section: Introductionmentioning
confidence: 99%